Design of Three-phase Auxiliary Inverter for Maglev Train - 谢湘剑; 林文彪 (Kongzhi Yu Xinxi Jishu)
It introduces a three-phase auxiliary inverter with DC1 500 V power supply. Compared with the traditional static auxiliary inverters, it is smaller and lighter. This product has been used in Maglev Train of Shanghai and Tangshan, and is stable and reliable.